A specific reconditioning training program implemented 12 months after ACL surgery improves lower-limb jump variables in amateur soccer players - Jiménez-Rubio, Sergio; García-Calvo, Tomás; Martínez-Aranda, Luis Manuel; Raya-González, Javier (Frontiers in Physiology, 2025)
IntroductionIntroduction Soccer players are frequently exposed to high physical demands, which increase their risk of injury, especially anterior cruciate ligament (ACL) ruptures. Despite completing standard rehabilitation protocols, many athletes show persistent functional deficits one year after surgery. This study aimed to assess the impact of a 12-week reconditioning training program, focusing on adjacent joint mobility, neuromuscular control, plyometrics, stability-landing exercises, and strength production, of amateur soccer players 12 months after undergoing anterior cruciate ligament (ACL) surgery. MethodsTwenty-five Spanish male amateur soccer players (age = 21.2 ± 2.4 years) participated voluntarily. All participants followed similar return-to-play guidelines and were randomly assigned to either the control group (CG, n = 13) or the experimental group (EG, n = 12). Soccer players in the EG underwent the 12-week training program (ACLrPRO), and both groups completed jump battery tests before and after the intervention period. Results and discussion The results showed improvements in all analyzed variables for the EG, except for the time to stabilization during the single-leg land and hold test for their non-injured leg, where the CG showed better results. Moreover, players in the CG exhibited a decline in performance related to their non-injured leg across all performed tests. The EG also demonstrated lower absence days during the experimental period compared to the CG. These findings underscore the significance of implementing a targeted neuromuscular training program for soccer players recovering from an ACL rupture, especially in enhancing performance and reducing absence days after their return to competition.